Analisis Unsur Intrinsik Cerpen Leak Jegeg - I Nyoman Suka Ardiyasa; Ni Made Ayu Susanthi Pradnya Paramitha (Dharma Sastra: Jurnal Penelitian Bahasa dan Sastra Daerah, 2022)
Literature is always associated with creativity related to beauty. Literary works are born from a process of creation by humans. Literature itself is an expression from within humans so that literature tends to be free. In the world of literature, a writer has the right to convey something. There is no need for the approval of others to convey expression through literature. Literary works can be in the form of short stories, novels, fables, myths, fairy tales, and legends. This research will try to analyze a short story (short story) with the title Leak Jegeg. This research is a qualitative research and the method used is descriptive method. With the theory of structuralism, this paper will describe the intrinsic elements that build the short story.